FIELD NOTES: Challenges and Approaches for Collecting Recent Material Heritage of Science and Technology - Pantalony, David (Museologia e Patrimônio, 2015)
At the Canada Science and Technology Museum, we have been putting more emphasis on collecting and researching recent material heritage. There are enormous challenges associated with size and scope, geographical coverage, ownership, privacy, complexity of components, tracing supply chains, transportation, available storage space, decisions about significance, proprietary knowledge, safety, preservation, and objects that are opaque and inaccessible to the untrained eye. In this paper, I cover a variety of case studies of contemporary collecting and the strategies we are developing to turn these challenges into opportunities for research and sharing.